Prevalence of surgical site wound infection after spine surgery in nasal colonization of methicillin‐resistant Staphylococcus aureus: A meta‐analysis - Imam, Mohamed S.; Abdel‐Sattar, Randa M.; Alqarni, Faisal; Aljumayi, Saad Yousef S.; Altukhais, Ibrahim; Altukhays, Abdullah Saad; Abdelrahim, Mohamed E. A. (International wound journal, 2024)
The purpose of the meta‐analysis was to evaluate and compare the prevalence of surgical site infection (SSI) after spine surgery (SS) in nasal colonization of methicillin‐resistant Staphylococcus aureus (MRSA). The results of this meta‐analysis were analysed, and the odds ratio (OR) and mean difference (MD) with 95% confidence intervals (CIs) were calculated using dichotomous or contentious random‐ or fixed‐effect models. For the current meta‐analysis, 14 examinations spanning from 2014 to 2022 were included, encompassing 18 410 people who were tested for nasal colonization after SS. MRSA‐positive had a significantly higher SSI (OR, 3.65; 95% CI, 2.48–5.37, p < 0.001) compared with MRSA‐negative in SS subjects. However, no significant difference was found between methicillin‐susceptible Staphylococcus aureus and Staphylococcus aureus negative (OR, 0.94; 95% CI, 0.32–2.79, p = 0.91), and Staphylococcus aureus positive and negative (OR, 2.13; 95% CI, 0.26–17.41, p = 0.48) in SS subjects. The examined data revealed that MRSA colonization had a significant effect on SSI; however, methicillin‐susceptible Staphylococcus aureus and Staphylococcus aureus had no significant effect on SSI in SS subjects. However, given that some comparisons included a small number of chosen studies, attention should be given to their values.